The Clinical and Demographic Characteristics of Pediatric Behçet’s Patients - Hayriye Sarıcaoğlu; Hatice Erdem; Semra Çıkman Toker; Emel Bülbül Başkan; Şükran Tunalı; Ali Yücel (Güncel Pediatri)
Aim: In this study, we aimed to compare the clinical and demographic features of pediatric Behçet’s patients with those of adult age.Materials and Method: We examined the clinical and demographic features of the 18 and under 18-year-old children who were followed-up in the Behçet's Center of Uludağ University Medical Faculty between 1992 and 2007, retrospectively. The information of age, sex, presence of oral aphthous ulcers, genital ulcers, erythema nodosum, papulopustular eruption, pathergy test positivity, ocular, articular, neurological, gastrointestinal, renal involvements and HLA-B5 positivity were obtained from the medical charts of the patients.Results: There were 30 pediatric Behçet diagnosed according to the diagnostic criteria of International Study Group for Behçet's Disease. The mean age of the patients was 15.9. At the time of the diagnosis, most of the patients were aged between 17-18 (43.3%). There was only one patient under 10. Oral aphthae was observed in all, and genital ulceration or the scar of the ulcer was observed in 23 patients; 15 females, 8 males (76.6%). Ocular involvement was present in 18 patients; 8 females, 10 males (60%); erythema nodosum in 13 patients; 8 females, 5 males (43.3%), papulopustular eruption in 16 patients; 10 females, 6 males and pathergy test positivity in 12 patients; 7 females, 5 males (36.6%). Vascular symptoms were observed in 2 patients, arthralgia-arthritis in 15 patients and neurological involvement in 4 patients.Conclusion: In this study, it was concluded that ocular involvement was more frequent in Behçet’s patients aged between 0-18 than adult Behçet’s patients, but mucocutaneous findings had similar frequency. (Journal of Current Pediatrics 2008; 6: 89-93)